Full 3D numerical relativity simulations of neutron star–boson star collisions with BAM. (18th December 2018) - Dietrich, Tim; Ossokine, Serguei; Clough, Katy
Abstract: With the first direct detections of gravitational waves (GWs) from the coalescence of compact binaries observed by the advanced LIGO and VIRGO interferometers, the era of GW astronomy has begun. Whilst there is strong evidence that the observed GWs are connected to the merger of two black holes (BH) or two neutron stars (NS), future detections may present a less consistent picture. Indeed, the possibility that the observed GW signal was created by a merger of exotic compact objects (ECOs) such as boson stars (BS) or axion stars (AS) has not yet been fully excluded. For a detailed understanding of the late stages of the coalescence full 3D numerical relativity simulations are essential. In this paper, we extend the infrastructure of the numerical relativity code BAM, to permit the simultaneous simulation of baryonic matter with bosonic scalar fields, thus enabling the study of BS–BS, BS–NS, and BS–BH mergers. We present a large number of single star evolutions to test the newly implemented routines, and to quantify the numerical challenges of such simulations, which we find to partially differ from the default NS case. We also compare head-on BS–BS simulations with independent numerical relativity codes, namely the SpEC and the GRChombo codes, and find good general agreement. Finally, we present what are, to the best of our knowledge, the first full NR simulations of BS–NS mergers, a first step towards identifying the hallmarks of BS–NS interactions in the strong gravity regime, as well as possible GW and electromagnetic observables.